Spatiotemporal dynamics and humanitarian crisis in Bol (Chad): Satellite imagery analysis - Djako, Exaucé Gali; Aboukey, Gnimdou; Azianu, Komi Ameko; Klassou, Komi Sélom; Chenal, Jérôme (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of protracted humanitarian crises on urban development in Bol, a city in Chad’s Lake region, with a focus on spatial transformations and planning implications. The purpose is to assess how displacement-driven urbanization has altered land use patterns and to inform more adaptive urban planning in fragile contexts. A mixed-methods approach was adopted, combining satellite imagery (Landsat, 1992–2023), demographic data, field surveys, and displacement records. Land use and land cover changes were mapped using a supervised classification technique based on the Support Vector Machine (SVM) algorithm. The results show a significant urban expansion of 60.57% between 1992 and 2016, followed by a slower growth rate of 3.86% from 2016 to 2023, primarily at the expense of agricultural land (−25.64%), sandy soils (−59.52%), and wetlands (−94.33%). The planned resettlement of 6,860 internally displaced persons (IDPs) in 2024 is expected to require an additional 73.1 hectares, putting further pressure on local land and infrastructure. The study concludes that remote sensing offers a critical tool for monitoring urban change in crisis-affected regions and underscores the need for spatially informed, sustainable urban planning strategies in rapidly transforming and ecologically vulnerable urban areas.